Sonochemical Synthesis of CuO Nanoplatelets and Their Tribological Properties as an Additive in Synthetic Oil Using Reciprocating Tribometer - Siraj Azam; Sang-Shin Park (Lubricants, 2023)
This Research aimed to improve the tribological properties of commercially available lubricating oil (5W-40) by incorporating CuO nanoplatelets (NPs) synthesized using a simple and cost-effective sonochemical method. To evaluate the performance of the nanolubricant, a reciprocating tribometer was indigenously designed and developed to measure the coefficient of friction (COF) and wear tracks between two AISI 1045 steel surfaces. The CuO NPs were characterized using XRD to confirm their purity and phase, while SEM and FE-TEM were utilized to study their morphology and composition. Raman spectroscopy was used to reveal three distinct Raman active peaks of CuO at 283, 330, and 616 cm−1. Zeta potential measurements demonstrated good dispersion quality, with a value of 92.0 mV for 0.1% concentration. SEM and FE-TEM analysis of the nanolubricant showed the formation of a tribo-film over the CuO NPs and adding 0.1% CuO NPs reduced COF by 32%. These findings suggest that incorporating synthesized CuO NPs in commercially available lubricating oil can enhance its tribological properties, leading to improved machine efficiency and lifespan, as well as reduced energy demand. Overall, the study demonstrates the potential benefits of using CuO nanoplatelets as an additive in lubricating oil, which could have significant implications for the development of more efficient nanolubricants.